2022
DOI: 10.3389/fendo.2022.918869
|View full text |Cite
|
Sign up to set email alerts
|

The tumor microenvironment of hepatocellular carcinoma and its targeting strategy by CAR-T cell immunotherapy

Abstract: Hepatocellular carcinoma (HCC) is the major subtype of liver cancer, which ranks sixth in cancer incidence and third in mortality. Although great strides have been made in novel therapy for HCC, such as immunotherapy, the prognosis remains less than satisfactory. Increasing evidence demonstrates that the tumor immune microenvironment (TME) exerts a significant role in the evolution of HCC and has a non-negligible impact on the efficacy of HCC treatment. In the past two decades, the success in hematological mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 176 publications
0
15
0
Order By: Relevance
“…Further studies will help to establish whether ICB administration actively induces TLS formation, and if B lymphocytes and TLS creation have an active and beneficial role in immunotherapy response. In this way, clinical strategies based on drugs that modulate B lymphocytes or TLS formation have been studied extensively to fight solid tumors [ 102 , 106 , 107 ].…”
Section: Clinical Application and Future Perspective Of B Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies will help to establish whether ICB administration actively induces TLS formation, and if B lymphocytes and TLS creation have an active and beneficial role in immunotherapy response. In this way, clinical strategies based on drugs that modulate B lymphocytes or TLS formation have been studied extensively to fight solid tumors [ 102 , 106 , 107 ].…”
Section: Clinical Application and Future Perspective Of B Lymphocytesmentioning
confidence: 99%
“…Current studies have demonstrated a marked heterogeneity in HCC tumors and highlighted that the crosstalk between cancer cells and the liver microenvironment promotes tumorigenesis and HCC pathogenesis, by pushing cell proliferation, survival, and the ability of migration and evasion [ 108 ]. In detail, the TME in HCC appears to be immunosuppressive, promoting the proliferation, invasion, and metastasis of tumors [ 106 , 107 ]. Thus, a better characterization of the immune landscape of HCC at high resolution would facilitate refining patient stratification and identify putative immune-therapeutic targets in order to develop novel therapies for HCC.…”
Section: Effect Of B Cells On Primary Liver Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, while CEA levels may be increased in some cases of liver brosis in rats, it is not a reliable marker for the disease and cannot be used as a diagnostic tool. 12 Several prior research have reported the anti-cancer activity of so corals against several forms of cancer, including breast, lung, colon, and liver cancer. 20 Because of its different modes of action in liver cancer, the group treated with silymarin following development of liver brosis demonstrated improvement in AFP and CEA when compared to the acetaminophen group.…”
Section: In Vivo Evaluation Of the Hepatoprotective Ability Of S Glau...mentioning
confidence: 99%
“…The latter involves manipulating T cells in the laboratory to add artificial receptors that can invoke attacks against cancer cells ( 32 34 ). However, CAR-T therapy remains limited by the lack of appropriate targets in solid tumors ( 33 , 35 37 ). However, advanced-stage patients or those presenting with unfavorable tumors inevitably face disease progression with dire outcomes ( 38 40 ).…”
mentioning
confidence: 99%